Digitized Ration Products Distribution Using Android Application - A. V. Keerthana; Roopasree M; Madhu Kumar S; Rajesh A (International Journal on Orange Technologies, 2022)
Ration cards are official documents issued by the state governments in India to every household that is eligible to purchase subsidized food items (rice, sugar, wheat etc.) and fuel (kerosene) from the Public Distribution System (PDS). The process to avail these items is complex nowadays due to excess crowds in ration shops. To overcome this difficulty, a mobile application has been developed. The food items can be ordered online, and a set of time slots will be provided. One of the Time slots and dates should be chosen to collect the displayed items. The payment is made either by direct mode or Online mode. It also includes a “Free Home Delivery” service for senior citizens. It also avoids material latency by providing an equal distribution of items. Specific individual vendors keep up with each area. Thus, the public authority receives a message about the utilization of grains by individuals.